2020
DOI: 10.1172/jci.insight.94035
|View full text |Cite
|
Sign up to set email alerts
|

Aim2-mediated/IFN-β–independent regulation of gastric metaplastic lesions via CD8+ T cells

Abstract: Aim2 deletion exacerbates SPEM. We identified Aim2 in a screen of upregulated gastric genes in 2 mouse models of SPEM: (a) chronic (6-month) H. felis infection and (b) gastric tissue-specific overexpression of IFN-γ (H + / K +-ATPase-IFN-γ) (18) (Figure 1A). The upregulation of Aim2 in gastric tissue of chronically H. felis-infected mice at 6 months was corroborated by real-time quantitative PCR (RT-qPCR) (Figure 1B). To study the role of Aim2 in SPEM, we used mice deficient in Aim2 (B6.129P2-Aim2 Gt(CSG445)By… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 75 publications
0
33
1
Order By: Relevance
“…These changes were induced by CXCL16 from B cells. The authors concluded that Aim2 regulates CD8 + T‐cell infiltration independently of the inflammasome, and inhibits metaplasia via a novel mechanism 9 . Lv et al 7 also reported that gastric epithelial cell expression of MMP‐10 led to CXCL16‐mediated migration of CD8 + T cells into the H pylori‐ infected gastric mucosa.…”
Section: Immunologymentioning
confidence: 98%
“…These changes were induced by CXCL16 from B cells. The authors concluded that Aim2 regulates CD8 + T‐cell infiltration independently of the inflammasome, and inhibits metaplasia via a novel mechanism 9 . Lv et al 7 also reported that gastric epithelial cell expression of MMP‐10 led to CXCL16‐mediated migration of CD8 + T cells into the H pylori‐ infected gastric mucosa.…”
Section: Immunologymentioning
confidence: 98%
“…Not only in epithelial cells, but also in immune cells, AIM2 seems to have inflammasome-unrelated functions during gastrointestinal disease. A recent report showed that AIM2 indirectly regulates gastric CD8 + T cell frequency during gastritis [ 88 ]. This effect is mediated by AIM2 expression in B cells, where it suppresses CXCL16 production, reducing the accumulation of CD8 + T cells in the inflamed gastric mucosa [ 88 ].…”
Section: Inflammasome-independent Role Of Aim2 In Health and Diseamentioning
confidence: 99%
“…A recent report showed that AIM2 indirectly regulates gastric CD8 + T cell frequency during gastritis [ 88 ]. This effect is mediated by AIM2 expression in B cells, where it suppresses CXCL16 production, reducing the accumulation of CD8 + T cells in the inflamed gastric mucosa [ 88 ]. Furthermore, inflammasomes-independent functions of AIM2 have also been observed outside the gastrointestinal tract.…”
Section: Inflammasome-independent Role Of Aim2 In Health and Diseamentioning
confidence: 99%
“…Moreover, they showed that MiR130b plays an essential role in supporting metaplastic transformation and MDSC function 27 . El‐Zaatari et al demonstrated a novel function of absent in melanoma 2 (Aim2) that regulates gastric metaplastic lesions via CXCL16‐mediated CD8 + T cells during H. felis infection 28 . Another study investigated how β‐catenin signaling regulates the tumour immune microenvironment in the stomach using a murine gastric cancer model established by H. felis .…”
Section: Pathogenesis Of Non‐helicobacter Pylori Helicobacter Infectionsmentioning
confidence: 99%